Avoiding the new mediocre : Raising long-term growth in the Middle East and Central Asia - Mitra, Pritha; International Monetary Fund (Washington, D.C International Monetary Fund (IMF), 2016)
Raising the Middle East and Central Asia’s long-term growth prospects is critical for meeting the region's pressing need for jobs and higher living standards.
Chapter 1. Why raise long-term growth? -- Chapter 2. What matters for growth of productivity, employment and capital? -- Chapter 3. Reforms to unlock growth potential in the Middle East and Central Asia -- Chapter 4. Main finding and policy implications
Includes bibliographical references (p.33-36).
Keywords: Economic development; ECONOMIC DEVELOPMENT; ECONOMIC GROWTH; EMPLOYMENT; ECONOMIC CONDITIONS; MIDDLE EAST; CENTRAL ASIA